The effect of admitted patients in the emergency department on rates of hospital admissions - Fogarty, Eoin M (BMJ Publishing Group, 2013)
Emergency Department overcrowding with admitted inpatients is a common international occurrence. We undertook a retrospective review to compare patient admission rates from patients presenting to our Emergency Department with the level of overcrowding with admitted inpatients on that particular day in the Emergency Department. Over the 2-year study period there was no change in the rate or absolute number of admissions per day compared with the level of inpatient overcrowding.